Study Of The Effect Of The Number Of Coils On Voltage And Current Value - M Faqih; Angga Firnanda; Mohammad Salman Aji Arwangi (Fakultas Teknik Universitas PGRI Banyuwangi, 2023)
Transformers or often referred to as Transformers are electrical devices that can change the decrease and increase in AC voltage to DC. This transformer works on the principle of electromagnetic induction. Based on the results of the analysis of the calculation data, it can be concluded that the number of primary and secondary windings greatly affects the value of the voltage and current, this is in accordance with the theory, namely VP/VS = NP/NS = IP/IS